The Trinitarian testimony of the spirit : prosopological exegesis and the development of pre-Nicene pneumatology - Hughes, Kyle R. (Supplements to Vigiliae Christianae, 2018)
In The Trinitarian Testimony of the Spirit, Kyle R. Hughes offers a new approach to the development of early Christian pneumatology by focusing on how Justin, Irenaeus, and Tertullian linked the Holy Spirit with testimony to the deity and lordship of the Father and the Son. Drawing extensively on recent studies of prosopological exegesis and divine testimony in the ancient world, Hughes demonstrates how these three pre-Nicene Christian writers utilized Scripture and the conventions of ancient rhetoric and exegesis to formulate a highly innovative approach to the Holy Spirit that would contribute to the identification of the Spirit as the third person of the Trinity.